2012
DOI: 10.4046/trd.2012.73.6.325
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Radiation Bronchitis Induced Massive Hemoptysis after High-Dose-Rate Endobronchial Brachytherapy

Abstract: High-dose-rate endobronchial brachytherapy (HDREB) have been used as the treatment of early endobronchial cancer, as well as for palliation of advanced cancer. However, fatal hemoptysis can occur after HDREB at the rate of 7~32%. We report a case of massive hemoptysis due to radiation bronchitis developed after HDREB. A 67-year-old man was treated with HDREB for early endobronchial cancer on the left upper lobe bronchus. He complained of persistent cough from 4 weeks after completion of HDREB. Radiation bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Endobronchial brachytherapy is a notable approach frequently employed to administer high doses of radiation in proximity to the primary tumor, applying high-dose rates to the tumor while sparing the surrounding normal tissue [ 15 , 22 ]. However, when a catheter is placed near the bronchial wall where a larger vessel exists, there is a considerable risk of bleeding, as well as potential late toxicities such as fistula formation, hemoptysis, tracheomalacia, and bronchial stenosis [ 27 , 28 , 29 , 30 ]. Furthermore, the procedures and outcomes of brachytherapy can vary substantially depending on the operator, and there may be substantial intra- or inter-fraction discrepancies and errors, rendering it less reproducible [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endobronchial brachytherapy is a notable approach frequently employed to administer high doses of radiation in proximity to the primary tumor, applying high-dose rates to the tumor while sparing the surrounding normal tissue [ 15 , 22 ]. However, when a catheter is placed near the bronchial wall where a larger vessel exists, there is a considerable risk of bleeding, as well as potential late toxicities such as fistula formation, hemoptysis, tracheomalacia, and bronchial stenosis [ 27 , 28 , 29 , 30 ]. Furthermore, the procedures and outcomes of brachytherapy can vary substantially depending on the operator, and there may be substantial intra- or inter-fraction discrepancies and errors, rendering it less reproducible [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation‐induced lung injuries mainly include radiation pneumonitis, lung fibrosis, and organizing pneumonia 6,7 . Radiation bronchitis with stenosis or granulation was reported in lung cancer patients, but they had received brachytherapy 3,4 or combined external‐beam and high dose‐rate iridium brachytherapy 8 . Radiation bronchitis was reported in esophageal cancer patients who had a total 68.4 Gy dose 9 …”
Section: Discussionmentioning
confidence: 99%
“…Thoracic radiotherapy may induce lung injuries, mainly radiation-induced pneumonitis, radiation-induced lung fibrosis, radiationinduced bronchiolitis obliterans organizing pneumonia, 1,2 and radiation-induced bronchitis. 3,4 We report two rare cases of radiation-induced pseudomembranous tracheobronchitis with or without bronchial obstruction in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported the use of EBBT for radical irradiation to eliminate tumors (Table 1). 6–11 However, adverse events (AEs) such as hemoptysis or severe bronchitis due to overdosing owing to uneven dose distribution in the bronchus have been a problem 12,13 . Thus, we have developed an applicator (Figure 1(a)) to keep the radioactive source in the center of the bronchial lumen (Figure 1(b)) and attempted to improve the dose distribution in the bronchial lumen 14 .…”
Section: Introductionmentioning
confidence: 99%